Optimization of microbial induced carbonate precipitation treatment process to improve recycled fine aggregate - Yuxi Zhao (Elsevier, 2021)
Microbial induced carbonate precipitation (MICP) is a novel and environmentally-friendly method to improve the properties of recycled aggregate. This study focused on the optimization of MICP treatment process, mainly including the modification duration, the addition method of calcium source and the number of modification cycles, to improve the quality of recycled fine aggregate (RFA). Weight increase and water absorption decrease of RFA after MICP modification were used to evaluate the effects on the improvement in properties of RFA. The properties of the mortar with modified RFA were examined to investigate the effectiveness of the proposed MICP treatment process. The results show that the optimal MICP treatment process consisted of disposable addition of calcium source and repeating 3 modification cycles with single modification duration of 1 d, verified by the SEM observation and XRD analysis; the mortar with RFA modified by the proposed MICP process showed higher flexural strength and carbonation resistance, which can be explained by the better pore structure at a microscopic level.